Experimental development of a Nusselt correlation for forced reciprocating oscillated vertical annular glycerol flow through a porous domain - Sayar, Ersin (Springer Science and Business Media LLC, 2017)
The objective of this paper is to investigate the heat transfer to oscillating annular flow of a viscous fluid. The flow media includes stationary stainless steel wool porous domain and glycerol as the working fluid. The effects of actuation frequency and wall heat flux on the temperature field and resultant heat convection coefficient are studied. The temperature values at radial direction are close each other as porous media mixes the glycerol successfully. A correlation with a functional dependence to kinetic Reynolds number is recommended that can be used to acquire the averaged heat transfer for oscillating flows. Present experimental results with glycerol in a porous media are compared to the published experimental works with water. For the limited case of the two working fluids, Nusselt number is normalized well using the Prandtl number (Pr0.67). Results are also compared to non-porous media study and heat transfer is found to increase up to a factor of five in porous media. The recommended correlation is claimed to have a significant role for anticipating heat transfer of oscillating viscous fluid not only at low frequencies but also at low heat fluxes in a porous and permeable solid media.